Implementasi Model Problem Based Learning dan Cooperative Learning untuk Meningkatkan Pemahaman Hak dan Kewajiban Siswa Kelas 3 Sekolah Dasar - Rona Nida Firnanda; Kadhita Chandra Hapsari; Rina Yuliawati; Susilo Tri Widodo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve third-grade students’ understanding of rights and obligations through the implementation of Problem Based Learning (PBL) and Cooperative Learning within a two-cycle Classroom Action Research design. The first cycle applied PBL to stimulate problem-solving skills, while the second cycle used Cooperative Learning to strengthen collaboration and conceptual comprehension. Data were collected through tests, observations, and documentation, and analyzed using descriptive qualitative and quantitative techniques. The results indicate a significant improvement in learning outcomes, shown by the increase in the average score from 61.94 on the pretest to 82.11 on the posttest, along with the rise of students achieving mastery from 1 to 17 students. These findings demonstrate that PBL and Cooperative Learning effectively foster active engagement, deepen conceptual understanding, and enhance students’ participation in learning activities.